Seeing the forst and the trees: balancing functional and integrative knowledge using large-scale simulations in capstone business strategy class - Stephen, John; Brown, Randy C.; Parente Diane H. (2002)
The purpose of capstone classes in business administration is to integrate prior coursework into a solid foundation from which to begin business careers. This study assesses the extent to which a large-scale simulation pedagogy results in students' acquisition of an integrative perspective by the end of the course. The authors empirically test three hypotheses that specifically involve the use of either a functional or an integrative lens. The results provide promising evidence that the large-scale simulation approach is effective in helping students recognize the importance of integrating functional knowledge and developing an integrative lens. - Reproduced.
Keywords: Management education